Examining the U-shaped relationship of sleep duration and systolic blood pressure with risk of cardiovascular events using a novel recursive gradient scanning model - Yang, Shuo; Zhang, Nanxiang; Liang, Zichao; Han, Yuduan; Luo, Hao; Ge, Yingfeng; Yin, Jianan; Ding, Chonglong; Li, Chao; Zhang, Qitong; Zhang, Jinxin (Frontiers in Cardiovascular Medicine, 2023)
Background: Observational studies have suggested U-shaped relationships between sleep duration and systolic blood pressure (SBP) with risks of many cardiovascular diseases (CVDs), but the cut points that separate high-risk and low-risk groups have not been confirmed. We aimed to examine the U-shaped relationships between sleep duration, SBP, and risks of CVDs and confirm the optimal cut-points for sleep duration and SBP.A retrospective analysis was conducted on NHANES 2007-2016 data, which included a nationally representative sample of participants. The maximum equal-odds ratio (OR) method was implemented to obtain optimal cut-points for each continuous independent variable. Then a novel "recursive gradient scanning method" was introduced for discretizing multiple non-monotonic U-shaped independent variables. Finally, a multivariable logistic regression model was constructed to predict critical risk factors associated with CVDs after adjustment for potential confounders.Results: A total of 26691 participants (48.66% were male) were eligible for the current study with an average age of 49.43±17.69 years. After adjustment for covariates, compared with an intermediate range of sleep duration (6.5-8.0 h per day) and SBP (95-120 mmHg), upper or lower values were associated with a higher risk of CVDs (adjusted OR (95% CI) for sleep duration was 1.20 (1.04-1.40), and 1.17 (1.01-1.36) for SBP).This study indicates U-shaped relationships between SBP, sleep duration and risks of CVDs. Both short and long duration of sleep/higher and lower BP are predictors of cardiovascular outcomes. Estimated total sleep duration of 6.5-8.0 h per day/SBP of 95-120 mmHg is associated with lower risk of CVDs.